Cold Cas: reevaluating the occurrence of CRISPR/Cas systems in Mycobacteriaceae - Brenner, Evan; Sreevatsan, Srinand (Frontiers in Microbiology, 2023)
Bacterial CRISPR/Cas systems target foreign genetic elements like phage, and regulate gene expression, even of the host by some pathogens. The system is a marker for evolutionary history, used for inferences in Mycobacterium tuberculosis for 30 years. However, knowledge about mycobacterial CRISPR/Cas systems remains limited. It is believed that Type III-A Cas systems are exclusive to M. canettii and the M. tuberculosis complex (MTBC) of organisms, and that very few of the >200 diverse species of non-tuberculous mycobacteria (NTM) possess any CRISPR/Cas system. This work sought unreported CRISPR/Cas loci across NTM to better understand mycobacterial evolution, particularly in species phylogenetically near the MTBC. Analysis of available mycobacterial genomes revealed Cas systems are widespread across Mycobacteriaceae, and that some species contain multiple types. Phylogeny of Cas loci shows scattered presence in many NTM, with variation even within-species, suggesting gains/losses of these loci occur frequently. Cas Type III-A systems were identified in pathogenic Mycobacterium heckeshornense and geological environmental isolate Mycobacterium SM1. In summary, mycobacterial CRISPR/Cas systems are numerous, Type III-A systems are unreliable as a marker for MTBC evolution, and mycobacterial horizontal gene transfer appears to be a frequent source of genetic variation.